Extraction, preservation and utilization of natural colour from marigold(Tagetus erecta L.) - Sreevidhya M. K (Department of Processing Technology,College of Horticulture, 2010)
A study on extraction, preservation, and utilization of natural colour from marigold (Tagetus erecta L.) was conducted at the Department of Processing Technology, College of Horticulture, Vellanikkara during 2007-2009. Method for extraction of natural colour from marigold was developed. Solvent extraction of cured marigold flower flour using acetone: hexane in the ratio 3:7 was found to be the best method. The extracted oleoresin was purified by saponifying with KOH and further ethanol wash to obtain pure crystalline lutein powder. The extracted colour was preserved as 1:2 lutein: soyabean oil solution packed in glass bottles and stored at room temperature. Lutein solution was found suitable for the application in the products like ice cream, yoghurt, oil etc. as these products contained high amount of fat where as found not suitable for aqueous products as this pigment is not water soluble. A concentration of 0.1 g gave the best colour in ice cream and yoghurt while 0.15g for oil. Natural coloured products were stable only for a short period compared to synthetic colour during storage also it degrade faster on exposure to light, heat compared to synthetic colours. The changes in natural colour was not due to the changes in pH of product but due to the external agents like light and heat. Sensory analysis of natural coloured as well as synthetic coloured ice cream and yoghurt revealed the superiority of natural colour in all the characters like colour, flavour, taste and consistency. During storage natural colour degraded faster than synthetic coloured products. Thus an enhanced stability of the colour with respect to light , heat etc. are to be developed to use these natural colour as a substitute for the synthetic colours.